Risk of Covid-19 Transmission During the Second Wave Outbreak in Sumbawa Island, Indonesia - Pranata, Satriya; Putra, Dewa Gede Sanjaya; Purwadi, Hendri; Pratiwi, Adekutari; Wulandari, Herlinda; Wu, Shu-Fang Vivienne (International Journal of Nursing and Health Services (IJNHS), 2022)
Introduction: Some countries reported second wave outbreaks of coronavirus. Objectives: To explore how dangerous the risk of COVID-19 transmission during the second wave outbreak in Sumbawa Island, Indonesia. Methods: A descriptive normative survey method to describe an object and behaviour in accordance with existing reality in Sumbawa Island. The number of respondents was 201 people who were given questionnaires by researchers. Results: Most of the respondents held the status of a State Civil Apparatus that is equal to 61.69%. In the second place, some respondents had the status of self-employed totalling 7.46%. Based on the type of work they did, the respondents had fairly high mobility at 89.55%. In addition, 89.05% of respondents have a habit of touching money or items that are touched by other people and this is exacerbated by the behaviour of not using hand sanitisers to clean their hands totalling 72.14% of respondents. Moreover, 86.57% of the respondents do not have the habit of sunbathing for 15 minutes per day and do not do sports for 30 minutes per day totalling 61.19% of respondents. Recommendation: High mobility, infrequent exercises, infrequent handwashing, and improper implementation of social distancing can increase the risk of COVID-19 infection. The government should conduct a campaign to spread the information in order to break the chain of risk of transmission